Social Media Marketing and Relationship Marketing on Adikara Batik’s Customer Engagemen - hassan, raden muhammad naufal ali; wijayanti, ra afera ratna (LIAISON JOURNAL OF BEST, 2025)
The globalization of commerce in the digital age has revolutionized the way businesses engage with their customers. As a traditional art form with deep cultural roots, Indonesian batik has not remained untouched by this transformation. This thesis aims to explore the multifacetedimpact of social media marketing on customer engagement within the Indonesian batik industry.As social media platforms continue to serve as prominent channels for brand promotion and customer interaction, this study delves into how the unique and intricate designs of Indonesian batik, coupled with strategic digital marketing, shape customer engagement and influenceconsumer behavior.The demographic being studied consists of people who have participated in Adikara Batik's online platforms, specifically Instagram and TikTok, and people who have attended workshop classes. The technique of purposive sampling is utilized to guarantee the incorporation of participants who genuinely exhibit curiosity and participation. In order to gain quantifiable insights into participants' opinions on Adikara Batik's social media marketing andtheir levels of engagement with the brand, data is gathered through an electronically disseminated, structured questionnaire. The study explores a variety of factors, such as consumer engagement measures like likes, comments, shares, and workshop attendance, as wellas social media marketing techniques, which include content relevancy, post frequency,interactive features, and promotional campaigns. The study attempts to identify patterns and correlations in the gathered data by combining descriptive and inferential statistical techniques. Strict adherence is made to ethical requirements, including as participant confidentiality, anonymity, and informed consent.There are numerous limitations to this research, including onewhich is its exclusive focus on Adikara Batik, which might limit the applicability of the findings to other sectors. Furthermore, response bias is introduced by the use of self-reported data. The study's findings are intended to be insightful and useful for Adikara Batik as well as the larger academic community. They will present complex viewpoints on how social media marketingaffects customer engagement in the context of traditional craftsmanship. Keywords: Social Media Marketing, Relationship Marketing, Customer Engagement, Content, Adikara Batik